Peningkatan Kemampuan Pedagogi Guru melalui Pembelajaran Berbasis Proyek di SMPN 6 Mataram - Rahayu, Satutik; Artayasa, I Putu; Hadi, Kasnawi Al; Zulkarnaen, Zulkarnaen (Jurnal Gema Ngabdi, 2025)
This community service program aims to enhance human resource quality at SMPN 6 Mataram through the implementation of project-based learning. Project-based learning focuses on engaging students in solving real-world problems, allowing them to develop not only academic skills but also practical experience in project management and teamwork. The program was implemented in several stages: planning, execution, and evaluation, with students actively involved in each phase. The results showed significant improvements in students' project management and teamwork skills. Additionally, the program had a positive impact on students' engagement in learning and opened up better future prospects for them. Overall, project-based learning has proven to be an effective strategy for improving human resource quality in the educational environment, especially at SMPN 6 Mataram.